PEMBAGIAN HARTA BERSAMA KARENA PERCERAIAN BAGI MASYARAKAT ADAT BATAK TOBA - Ardina Khoirun Nisa (Institut agama islam negeri Padangsidimpuan, 2021)
Marriage is a legal relationship that contains a legal relationship between a man and a woman who has fulfilled the conditions of marriage for the longest possible period of time, and is a choice of a man and a woman to form a bond to seek happiness. and also an eternal and harmonious home. For the people of Indonesia, it has been their guideline for a long time that marriage, birth and death are very much influenced by religious provisions. In addition to being in accordance with religion and beliefs when talking about marriage, it is also inseparable from the customary rules that govern it, this is because Indonesia has customs, culture, and a close background that underlies the life of its people. Every human being certainly hopes that his marriage will be well-knit until death separates. But the marital conditions that are lived do not always run harmoniously and are fine as expected. Sometimes if misunderstandings and conditions that occur in the household cannot be resolved by way of peace for the common good, then a way is chosen to separate or divorce is carried out. The customary rules that are binding in life depend on the community (or part of the community) who support these customs which are primarily based on the justice of their customary law, including the Toba Batak customary law.The type of research in this article is a sociological or empirical juridical research method. The nature of this research is descriptive analytical. The results of the research found were that the distribution of joint assets due to divorce based on Law No.1 of 1974 concerning Marriage regulates the implementation as in Article 37 which states that if a marriage breaks up due to divorce, the assets are regulated according to their respective laws (religious law, law adat, court decisions). Disputed assets are classified as shared assets during marriage. The distribution of joint assets is then assessed for the amount to be divided by half against the parties. After the dissolution of the household, their common wealth is divided in half between husband and wife or between their heirs, regardless of which party the goods originate from.